Human-Nature Ecological Interaction of African Traditional Community in Chinua Achebe’s Things Fall Apart (Literary Ecology Approach in Literature) - Hadiyanto Hadiyanto (EDP Sciences, 2021)
This research paper discusses the ecological interaction between humans and nature in African traditional Ibo tribe community as described in a literary work of Chinua Achebe’s Things Fall Apart by using literary ecology approach in literature. The result of the research indicates that African traditional tribe community has a good, intense interaction and has a harmonious life with nature, for instances, they learn to mingle familiarly with dry season, rainy season, and harmattan season for a successful farming method and harvest of yam, they also learn to interact very well with various kinds of vegetations such as bamboo, kola nut, banana leaves, grasses, roots, barks of trees to fulfil their life necessities, and they learn to have knowledge for an effective interaction and good usage of animals for ritual and meal, especially goat and locust. African traditional community also has a strong commitment to keep the harmonious relationship with nature by maintaining a life balance with nature including vegetation and animal, to enjoy living in happiness with nature by warmly welcoming various seasons, such as rainy season, dry season, and the cold dusty harmattan season, and to maintain natural resources friendly and wisely in clearing the new land for planting staple-food plants and other supporting plants sufficiently.